Professional development short scale: Measurement invariance, stability, and validity in Brazil and Angola - Mourão, Luciana; Tavares, Susana M.; Sandall, Hugo (Frontiers in Psychology, 2022)
Professional development is the vital process in the workplace that comprises the growth and maturation of knowledge, skills, and attitudes arising from formal and informal learning at work throughout one’s life. The goal of this research was to present validity evidence and accuracy of the Professional Development Short Scale (PDSS) for different occupational categories. The research was conducted using four cross-sectional questionnaire surveys with convenience samples of different occupational categories (N = 2,547) in 41 cities throughout Brazil and Angola. The first study aimed to explore the factorial structure and internal consistency of the PDSS. The second study aimed to evaluate the cross-cultural validity and measurement invariance of the scale. The third study was to assess concurrent validity and predictive validity. The fourth study was to assess the test–retest reliability. The results indicated a one-factor structure, with six items for both countries’ datasets. This research pointed out the validity of the PDSS as regards its convergence-discriminant pattern with the General Self-Efficacy and Job Self-Efficacy Scales, and also, the relationship of the PDSS with relevant constructs (Bases of Power/leadership styles, In-role performance, Job Satisfaction, and Career Promotion). In this study, we provide psychometric validity of the Professional Development Short Scale to offer it as a resource to measure the construct and allow researchers to apply it in research models easily integrated to other constructs. We covered several different incremental approaches to ensure the scale validity. Besides showing temporal stability to ensure it can be applied from time to time, as one dynamic construct should, we also indicated that social desirability did not influence the measurement of the PDSS. Furthermore, the results indicate that the effects of the method do not generate undue confusion on the scale. Thus, the psychometric properties of the PDSS allow for recommending the use of the scale in extensive studies. This scale therefore contributes to contemporary professional development literature through the comparison of the perceptions of professional development in different professional categories and by providing organizational researchers with a tool to evaluate the effects and predictors of such construct.